2022
DOI: 10.1111/irv.12998
|View full text |Cite
|
Sign up to set email alerts
|

International changes in respiratory syncytial virus (RSV) epidemiology during the COVID‐19 pandemic: Association with school closures

Abstract: Background Little RSV activity was observed during the first expected RSV season since the COVID‐19 pandemic. Multiple countries later experienced out‐of‐season RSV resurgences, yet their association with non‐pharmaceutical interventions (NPIs) is unclear. This study aimed to describe the changes in RSV epidemiology during the COVID‐19 pandemic and to estimate the association between individual NPIs and the RSV resurgences. Methods RSV activity from Week (W)12‐2020 to W44‐2021 was compared with three pre‐pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…A good surveillance system is especially important, since RSV circulation has been altered due to the COVID-19 pandemic. During 2020-2021, RSV season was either completely missed (Brazil, Chile, Japan, Canada and South Korea) or delayed by an average of 39 weeks due to the effect of the nonpharmacological contingency interventions (social isolation, movement and gathering restriction, school and workplace closing, face-mask policies) [44][45][46][47]. The virus resurged after restrictions were lifted and schools reopened [48].…”
Section: Discussionmentioning
confidence: 99%
“…A good surveillance system is especially important, since RSV circulation has been altered due to the COVID-19 pandemic. During 2020-2021, RSV season was either completely missed (Brazil, Chile, Japan, Canada and South Korea) or delayed by an average of 39 weeks due to the effect of the nonpharmacological contingency interventions (social isolation, movement and gathering restriction, school and workplace closing, face-mask policies) [44][45][46][47]. The virus resurged after restrictions were lifted and schools reopened [48].…”
Section: Discussionmentioning
confidence: 99%
“…With the relaxation of NPIs and waned immunity in young children may lead to the resurgence of respiratory virus infection, and even lead to larger or more severe outbreaks, especially in children. 40,41…”
Section: Discussionmentioning
confidence: 99%
“…Reicherz et al 39 have found that HRSV antibody levels and neutralization were reduced in women and infants 1 year into the COVID‐19 pandemic compared to earlier in the pandemic. With the relaxation of NPIs and waned immunity in young children may lead to the resurgence of respiratory virus infection, and even lead to larger or more severe outbreaks, especially in children 40,41 . Therefore, ongoing surveillance for HIFV, HRSV, HMPV, and other respiratory viruses is important during and after the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A trend in delayed or missed RSV epidemics was observed worldwide after the first COVID-19 pandemic wave, and school re-opening was one of the non-pharmaceutical interventions associated with increased RSV circulation [ 20 ]. Contrary to this other than our results, France reported an RSV epidemic during the winter 2020–2021, just after the end of the lockdown.…”
Section: Discussionmentioning
confidence: 99%